Australia Makes a U-Turn with the Revival of the Pacific Solution: Should Asylum Seekers Find a New Destination? - Kaitlyn Pennington-Hill (Washington University Global Studies Law Review, 2014)
The purpose of this Note is to examine how, if at all, the reintroduced Pacific Solution differs from the highly criticized Pacific Solution of the Howard Government, and whether the Pacific Solution serves its purpose of discouraging new arrivals.15 Part II of this Note provides a historical overview of Australia’s refugee policy and the Pacific Solution; Part III examines international law relating to the Pacific Solution and the humanitarian and economical issues involved in such examination; and Part IV recommends changes that should be made to the Pacific Solution to ensure that Australia’s U-turn is a step in the right direction.
Keywords: immigration; visa; UNHRC; refugee; policy; asylum; human rights; Pacific Solution; Australia